Finite element simulation of orthogonal machining of biomedical grade Co–Cr–Mo alloy. (January 2020) - Trimble, D.; Agarwal, A.; McDonnell, D.; Barron, S.; Ahearne, E.; O'Donnell, G.E.
Abstract: Cobalt–chromium–molybdenum ( Co–Cr–Mo ) alloys are used extensively within the biomedical industry for hip, knee and shoulder prostheses. These components are manufactured using a range of different processes which includes machining. However, material properties such as high hardness, high wear resistance and strain rate hardening classifies these alloys as difficult to cut materials. Finite Element ( FE ) Modelling of machining processes can reduce the number of machining tests required for optimisation. The aim of the present work was to develop a FE model that can predict the orthogonal forces during the machining of biomedical grade Co–Cr–Mo alloy. To achieve this, it was necessary to develop the constitutive material model for this alloy. A modified Zerilli–Armstrong model was found to have the greatest predication capability compared to a modified Johnson–Cook and a strain compensated Arrhenius-type model. An orthogonal cutting finite element model was developed using Deform 3D over a range of different feed rates and cutting speeds. The model predicted the cutting forces to a high degree of accuracy (less than 5% error) over a range of different feed rates at low cutting speeds.